Combined immunohistochemical and immunofluorescence method to determine the phenotype of proliferating cell populations. Issue 11 (November 1992) - Ramshaw, A L; Parums, D V
Abstract : AIMS: To determine the phenotype of proliferating cell populations. METHODS: The double immunostaining technique combines the autofluorescent properties of alkaline phosphatase substrate naphthol/Fast Red with immunofluorescence using fluorescein. Fresh human tonsil and fresh atherosclerotic aortic aneurysm wall tissue were studied using a panel of monoclonal antibodies including Ki-67, CD4, CD8, CD19, CD22, HLA-DR alpha, CD68 and CD31. RESULTS: This double immunostaining method permitted simultaneous colocalisation of different markers on the same cell and could be used to identify HLA-DR positive cells as well as proliferation associated Ki-67 positive cells in human tonsil tissue and in chronic periaortitis associated with advanced atherosclerosis. CONCLUSION: This technique is simple and the results may be viewed using a single fluorescence filter. The Fast Red reaction product is stable and does not fade under storage. The staining works particularly well with markers for nuclear antigens in combination with markers for cytoplasmic or surface antigens.